Achieving highly thermal conductivity of polymer composites by adding hybrid silver–carbon fiber fillers. (April 2022) - Wu, Xinfeng; Shi, Shanshan; Tang, Bo; Chen, Jin; Shan, Liming; Gao, Yuan; Wang, Ying; Jiang, Tao; Sun, Kai; Yang, Ke; Yu, Jinhong
Abstract: Multi-dimensional filler networks composed of 0D Ag nanoparticles (AgNPs), 1D Ag nanowires (AgNWs) and carbon fibers (CFs) were designed and fabricated as thermally conductive fillers for epoxy matrix. The CFs were decorated with AgNPs to increase the effective thermally conductive pathways between CFs. A small quantity of AgNWs (only 3 wt%) doped into AgNPs decorated CFs mats could dramatically increase epoxy thermal conductivity. The through-plane thermal conductivity of the epoxy composites with AgNP@CF/AgNWs networks could reach 0.76 W/(m·K), nearly 3 times of neat epoxy and more than 50% improvement compared with CF based composite without Ag, demonstrating high efficiency of thermal conductivity improvement of 0D and 1D Ag. Moreover, as vertical heat transfer, the epoxy nanocomposites reveal improved thermal management capability compared with CF based composite, showing strong potential for efficient cooling. Highlights: Multi-dimensional and thermally conductive filler networks composed of 0D Ag nanoparticles (AgNPs), 1D Ag nanowires (AgNWs) and carbon fibers (CFs) were designed. The CFs were decorated with AgNPs to increase the effective thermally conductive pathways between CFs. The novel multi-dimensional filler networks can significantly increase the thermal conductivity of epoxy with little filler loading.